MAKING SENSE OF FLOUTING CONVERSATION MAXIMS OF TEACHER-STUDENT INTERACTIONS IN MOVIES: A MIXED METHODS - NGO, CRISTY GRACE A; Caballo, John Harry S; Navarro, Ana Louella N. (International Journal of Language and Literary Studies, 2023)
This mixed methods study, employing embedded design, aimed to ascertain the evident flouting maxim statements by the teachers and students during classroom interaction as depicted in five selected movies and how teachers and students react to and use flouting maxim statements. It also aimed to determine the significant difference between the occurrence of observed and non-observed flouting in classroom interactions. Results yielded that out of the 35 dialogues, 11 dialogues observed the cooperative principle and its conversation maxims while 24 dialogues deviated. Through IDI and FGD, the researcher unearthed the six essential themes in teachers' and students' reactions to and use of flouting maxim statements. Results revealed that there is no significant difference in the number of observed flouting maxims between teachers and students in terms of maxims of quality, quantity, relation, and manner. In integrating the data, three focal points were obtained namely: the sensitivity of students over teachers in detecting flouting maxims, no significant difference in the detection of flouting maxims in a classroom interaction, and teacher and student almost significantly differ in detecting the maxim of relation. In all the focal points, the nature of data integration is embedding.